2015
DOI: 10.4187/respcare.03457
|View full text |Cite
|
Sign up to set email alerts
|

Spirometry Quality in Adults With Very Severe Lung Function Impairment

Abstract: BACKGROUND: Some technologists worry that patients with very severe lung disease are unable to complete several spirometry maneuvers, which require considerable effort. METHODS: We retrospectively selected all spirometry tests with an FEV 1 < 35% predicted done by adult subjects sent to our pulmonary function laboratory during a 3-y period. We determined the rates and correlates of poor quality test sessions. RESULTS: Approximately 90% of the tests done by the 558 subjects with very severe lung-function impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A large occupational health study in an older population (mean age, 63 yr) found that 53% of spirometry maneuvers failed to reach a plateau despite encouragement by trained operators and long FETs ( 72 ). However, in another study, 90% of patients with severe lung function impairment were able to meet the criteria ( 81 ). Other large adult population studies found that more than 95% of subjects who expired for longer than 6 seconds achieved a plateau ( 82 , 83 ).…”
Section: Fev 1 and Fvc Maneuvermentioning
confidence: 97%
“…A large occupational health study in an older population (mean age, 63 yr) found that 53% of spirometry maneuvers failed to reach a plateau despite encouragement by trained operators and long FETs ( 72 ). However, in another study, 90% of patients with severe lung function impairment were able to meet the criteria ( 81 ). Other large adult population studies found that more than 95% of subjects who expired for longer than 6 seconds achieved a plateau ( 82 , 83 ).…”
Section: Fev 1 and Fvc Maneuvermentioning
confidence: 97%
“…Primarily, the results of our study show that implementation of such a pathway into the infrastructure of the cardiology department is feasible, with AF nurses being able to supervise the handheld (micro) spirometry and achieving valid results according to device standards in 89% of patients, comparable to conventional spirometry. 21 , 35 , 36 Moreover, airflow limitation was identified in one out of five patients.…”
Section: Discussionmentioning
confidence: 93%
“…Further studies can examine if spirometry interpretation criteria can be re-evaluated to accommodate suboptimal performance during pregnancy such as exploring the potential of using grade D under certain conditions. Although disregarded, the potential of lowering quality control criteria has been evaluated previously (20).…”
Section: Discussionmentioning
confidence: 99%